2015
DOI: 10.14716/ijtech.v6i5.1840
|View full text |Cite
|
Sign up to set email alerts
|

Key Performance Indicators Development for Government Agency

Abstract: Organizations perform all activities and operations within a framework, which are built on its vision and mission. The performance of each activity and operation can be measured using Key Performance Indicators (KPI), which indicate the organization's success in achieving its strategic objectives. KPI is widely used not only by profit-oriented organizations, but also by non-profit organizations such as government agencies. Government agencies have different characteristics in terms of funding, programs, and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Results shown in table 1 indicated that they are applying all four perspectives of BSC unknowingly. These results agree with the previously stated in the literature review (Nurcahyo, Wibowo, & Putra, 2015;Rasoolimanesh, Jaafar, Badarulzaman, & Ramayah, 2015) which clarified that a clear and announced vision and mission are the basic requirements for implementing BSC in the large and small organizations. These results are consistent with Giannopoulos et al (2013) who clarified that companies don't focus only on financial indicators to direct their strategic vision and to determine the satisfaction of customers and employees.…”
Section: The Opportunities For the Bsc Application In Egyptian Travelsupporting
confidence: 92%
“…Results shown in table 1 indicated that they are applying all four perspectives of BSC unknowingly. These results agree with the previously stated in the literature review (Nurcahyo, Wibowo, & Putra, 2015;Rasoolimanesh, Jaafar, Badarulzaman, & Ramayah, 2015) which clarified that a clear and announced vision and mission are the basic requirements for implementing BSC in the large and small organizations. These results are consistent with Giannopoulos et al (2013) who clarified that companies don't focus only on financial indicators to direct their strategic vision and to determine the satisfaction of customers and employees.…”
Section: The Opportunities For the Bsc Application In Egyptian Travelsupporting
confidence: 92%
“…Despite the large number of solutions and government programs that have been adopted at the highest level in order to transition into a digital government, several problems remain, which have led to an increase over past 10 years in the number of studies and developments surrounding this issue. The goals of most of the related research can be divided into two broad groups: (a) defining the theoretical foundations and main problems of a digital transformation, including the area of public administration (Petrov et al, 2016;Bataev, 2018;Bataev et al, 2018;Woodhead, 2018;Sankowska, 2018); and (b) assessing the maturity levels of a digital economy as a whole and, in particular, of digital public administration as one of digital transformation's main elements (World Bank., 2018;Mahesa et al, 2019;Sidorenko et al, 2019;Nurcahyo, R. et al, 2018). Bataev et al (2018) and Petrov et al (2016) indicated the following basic problems of developing an e-government in Russia: (a) a lack of common reform strategy adopted across all three levels of power; and (b) regions' developing their own platforms.…”
Section: Methodsmentioning
confidence: 99%
“…Public reforms based on the management of resources of public institutions and strategic planning to increase these resources began in the 1990s. Therefore, it is very important to use transparent and accountable systems (Deryl & Tuivaiti, 2012), (Nurcahyo, Wibowo, & Putra, 2015). Norton and Kaplan's BSC has been modi ed for the public sector, as the public sector is not for pro t. The mission of the public sector is to increase resources, increase the quality of service provided to citizens and ensure citizen satisfaction (Deryl & Tuivaiti, 2012).…”
Section: The Balanced Scorecard In the Public Sectormentioning
confidence: 99%